Sweet chestnut (Castanea sativa Mill.) in Britain: its dendrochronological potential. Issue 2 (3rd April 2017) - Jarman, Rob; Moir, Andy K.; Webb, Julia; Chambers, Frank M.
Abstract: In Britain, where sweet chestnut is classified as an archaeophyte of Roman introduction, there are many ancient sweet chestnut trees and woodlands significant for conservation, yet no dendrochronological assessment has been made of them. This paper describes an attempt to assess the dendrochronological potential of sweet chestnut wood. Eight sweet chestnut trees (veteran trees in parkland and mature trees and coppice-grown stems in woodland) from five sites in western England were sampled by coring living wood and by cutting sections in fallen dead wood, to enable microscopic analysis of growth ring parameters. Four trees from three sites were cross-matched to form a 295-year chronology from AD 1716 to AD 2011. The annual resolution of the chronology was confirmed by regional cross-dating with oak reference chronologies. The ages for these chestnut trees range from circa AD 1668 to AD 1940. It is concluded that oak reference chronologies can be used to date sweet chestnut wood, with benefits for archaeological, historic building and palaeoenvironmental assessments. The extraction of sawn sections from dead veteran trees and their dendrochronological analysis indicates a more reliable and benign approach to dating ancient trees in historic landscapes compared with coring.